Senior High School Students Problem Solving in Terms of Mathematical Abilities - Rusydah Kamilah; Tatag Yuli Eko Siswono; Agung Lukito (Universitas Sebelas Maret, 2022)
Practicing problem-solving can increase students' confidence outside of the mathematics field. Meanwhile, students who have different mathematical abilities have different problem-solving abilities in solving problems. Therefore, this research aims to describe students' problem-solving abilities in terms of mathematical abilities by using qualitative descriptive research methods. The subjects were three students with high, medium, and low abilities, while the main instrument was the researcher himself, supported by test and interview instruments. The results of high and moderate students exploring and understanding the problem showed the reluctance to write in detail on the answer sheet for the information known and problem asked in the questions, then delivered it in the interview session. In contrastNTS, the low-ability students wrote in great detail. At the stage of representing and formulating, high, medium, and low students used the same terms and formulas. At the stage of planning and implementing, the three students used various methods. However, the three students acquired the same answer and rechecked the results with what was known in the questions.